Mail order wife [videorecording (DVD)] - Botko, Huck; Botko, Huck; Gurland, Andrew, 1971-; Gurland, Andrew, 1971-; Gurland, Andrew, 1971-; Yuan, Eugenia; Martinez, Adrian (Actor) (Distributed by Visual Entertainment, 2005)
A bachelor looking for a wife agrees to be filmed for a mock documentary as he gets a mail order bride. His new wife is convinced he wants a maid more than anything. A dark comedy about how hard it is to find love, especially from a catalogue.